Pengukuran Perbedaan Rasa Malu dan Self-Esteem Serta Kaitannya dengan Prestasi Akademis (Studi pada Remaja Korban Perceraian di Jakarta) - Rahmah Hastuti; Yohanes Budiarto (Fakultas Psikologi Universitas Tarumanagara, 2014)
Parental divorce psychological impact for children and adolescents. This study examines the differences are shame and self-esteem to the learning achievement of students who are teenagers, whose parents divorced. The shame is the emotional aspects that influence individual assessment of himself when dealing with others. The shame is an emotion that is typical of the growing of early interpersonal experiences when indvidu related by family or peers. The study involved participants aged teens because adolescence is a phase turbulent emotions, so that the basic emotions experienced by adolescents is an aspect that can be developed through the development of models of measuring instruments associated with the emotions of shame and self-esteem and the use of a secondary form of data measuring learning achievement teens. The study involved 184 adolescents with divorced parents have negative correlation between shame and self-esteem. The higher the shame teenager because her parents divorce, the more negative the adolescent self-evaluation. However, the two variables are not correlated with academic achievement grades obtained from past research participants.Keywords: shame, self-esteem, academic achievement, adolescent